The Role of Securities in the Optimal Allocation of Risk-bearing - Arrow, K. J. (Review of Economic Studies, 1964)
Journal Article The Role of Securities in the Optimal Allocation of Risk-bearing Get access K. J. Arrow K. J. Arrow Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 2, April 1964, Pages 91–96, https://doi.org/10.2307/2296188 Published: 01 April 1964